PHARMACOECONOMIC ANALYSIS OF ANTIHYPERTENSIVE DRUG COMBINATIONS USE - E. I. Tarlovskaya; Y. A. Balandina; N. S. Maximchuk-Kolobova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To pursue pharmacoeconomic analysis of two drug combinations of ACE inhibitor (enalapril) and diuretic.Material and methods. Patients with arterial hypertension degree 2 and diabetes mellitus type 2 without ischemic heart disease (n=56) were included into the study. Blood pressure (BP) dynamics and cost/effectiveness ratio were evaluated.Results. In group A (fixed combination of original enalapril/hydrochlorothiazide) 61% of patients achieved target BP level with initial dose, and the rest 39% of patients – with double dose. In group B (non-fixed combination of generic enalapril/indapamide) 60% of patients achieved the target BP with initial dose of drugs, 33% - with double dose of ACE inhibitor, and 7% - with additional amlodipine administration. In patients of group A systolic BP (SBP) reduction was 45.82±1.23 mm Hg by the 12th week vs. 40.0±0.81 mm Hg in patients of group B; diastolic BP (DBP) reduction was 22.47±1.05 mm Hg and 18.76±0.70 mm Hg, respectively, by the 12th week of treatment. In the first month of treatment costs of target BP achievement was 298.62 rubles per patient in group A, and 299.50 rubles – in group B; by the 12th week of treatment – 629.45 and 631.22 rubles, respectively. Costs of SBP and DBP reduction by 1 mm Hg during 12 weeks of therapy were 13 and 27 rubles per patient, respectively, in group A, and 16 and 34 rubles per patient, respectively, in group B.Conclusion. The original fixed combination (enalapril+hydrochlorothiazide) proved to be more clinically effective and more cost effective in the treatment of hypertensive patients in comparison with the non-fixed combination of generic drugs (enalapril+indapamide).